2010
DOI: 10.1136/qshc.2008.028407
|View full text |Cite
|
Sign up to set email alerts
|

Real-time clinical alerting: effect of an automated paging system on response time to critical laboratory values--a randomised controlled trial

Abstract: The automated paging system reduced the length of time physicians took to respond to critical laboratory values, but this difference was not statistically significant. Future reseach should evaluate the effects of alerts for conditions that currently do not generate a phone call and the addition of real-time decision support to the critical value alerts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…Automated clinical surveillance systems are effective for a variety of clinical conditions including the identification of sepsis (19), adverse drug reactions (20,21), and more recently, AKI (22,23). These surveillance systems have assisted with faster identification of events compared with usual care that has been shown to improve shortterm progression of AKI severity (22,24,25). Future studies are needed to determine the effect of clinical surveillance systems used to detect AKI on long-term recovery of renal function, as well as how these systems can be further refined to enhance the detection and management of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Automated clinical surveillance systems are effective for a variety of clinical conditions including the identification of sepsis (19), adverse drug reactions (20,21), and more recently, AKI (22,23). These surveillance systems have assisted with faster identification of events compared with usual care that has been shown to improve shortterm progression of AKI severity (22,24,25). Future studies are needed to determine the effect of clinical surveillance systems used to detect AKI on long-term recovery of renal function, as well as how these systems can be further refined to enhance the detection and management of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…As Etchells et al [12] Laboratory medicine communities of practice may profit from the work already completed in other safety-critical industries. It would be worthwhile to review which of the effective practices developed in other industries can be translated to laboratory medicine critical value reporting.…”
Section: Future Research Needsmentioning
confidence: 99%
“…Table 1 provides the summary effectiveness data for the practice of automated notification. Etchells et al [12] reported the results of a computer system-driven paging system for communicating 165 critical values for 108 patients. After implementing an automated notification system, the median interval decreased from 39.5 to 16 minutes (p=0.33) between placement of the critical value into the laboratory information system to the writing of an order on the patient's chart in response to the critical value.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Contacting a community requestor out of office hours requires substantial staff resource. It can be difficult to locate requestors 3,4 because after hours contact details have not been made available, the mobile phone has been switched off or the voicemail option is kept activated, the requestor is on leave or the duty doctor for a practice may refuse to accept the results because the patient is not known to them. Additionally, there may be uncertainty about the significance of the results.…”
Section: Introductionmentioning
confidence: 99%